Growth, carcass yield and thigh skin tensile strength of four commercial broiler strains - Kenmuir, Mare Desire (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1993.